2013
DOI: 10.4062/biomolther.2013.063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Fat Diet-induced Obesity on the Plasma Levels of Monoamine Neurotransmitters in C57BL/6 Mice

Abstract: Obesity is one of the most serious health problems in developed countries. It negatively affects diverse aspects of human wellbeing. Of these, a relationship between obesity and depression is widely recognized but biomarkers for assessment of obesityassociated mood changes in animal obesity models are rarely known. Here we explored the link between obesity and the plasma levels of monoamine neurotransmitters involved in mood control using a sensitive UPLC/MSMS technique in high fat diet (HFD)- induced obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
3
17
0
1
Order By: Relevance
“…The increased levels of serum TC, LDL, and HDL in the high-fat diet groups were similar to previous studies using the same high fat diet (D12492, Research Diets Inc., USA) [ 47 49 ]. The lower levels of total antioxidant capacity (TAC) in the high-fat diet group, were also in agreement with previous studies demonstrating a reduced antioxidant capacity as a result of obesity [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…The increased levels of serum TC, LDL, and HDL in the high-fat diet groups were similar to previous studies using the same high fat diet (D12492, Research Diets Inc., USA) [ 47 49 ]. The lower levels of total antioxidant capacity (TAC) in the high-fat diet group, were also in agreement with previous studies demonstrating a reduced antioxidant capacity as a result of obesity [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…Given the beneficial role of the serotonin (5-HT) system in the enhancement of brain plasticity (Quesseveur et al, 2013), the possibility that deficits in 5-HT neurotransmission underlie the comorbidity between T2D/IR and depression, has been raised. Consistent with this hypothesis, decreased levels of tryptophan were detected in the CNS of patients with T2D (Kloiber et al, 2010;Herrera-Marquez et al, 2011) or in rodents fed an HFD (Kim et al, 2013;Derkach et al, 2015). Using intracerebral microdialysis, we showed that mice fed an HFD displayed lower basal hippocampal extracellular 5-HT concentrations (Zemdegs et al, 2016).…”
Section: Introductionsupporting
confidence: 72%
“…Indirect evidence, however, is in favour of an attenuation of serotonergic tone because decreased levels of free tryptophan were detected in the CNS of patients with T2DM (Kloiber et al, 2010;Herrera-Marquez et al, 2011). Accordingly, a significant decrease in plasma or brain levels of 5-HT has been reported in rodents after prolonged HFD exposure (Kim et al, 2013;Derkach et al, 2015), but these neurochemical changes have never been confirmed using in vivo microdialysis.…”
Section: Introductionmentioning
confidence: 99%